PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA DENPASAR TERHADAP PENJABARAN PERATURAN KEPALA DAERAH TENTANG APBD - Juliarta, I Komang; Wairocana, I Gusti Ngurah; Suharta, I Nengah (Kertha Wicara : Journal Ilmu Hukum, 2013)
Regional Parliament (House of Representatives) in this case supervising in order to create good governance, oversight will be able to create a clean government and protected from corruption. Instead of that, the institution that participating in corrupt practices would not be able to do good supervision, the monitoring should be done properly by the existing rules. Further legal action formulated on How Denpasar Government in elaborating or implementing regulation Regional Head of Budget and How forms surveillance conducted Denpasar City Council on the elaboration and implementation of the Regulation of Regional Head of Budget. types of research used in writing this paper is a type of normative legal research. Major Regulation No. 44 in 2011 on the translation of Revenue and Expenditure Denpasar formed because given its strategic presence Regulation District / City of budgets, and oversight by parliament to Denpasar Denpasar District Regulation on the translation of budget oversight shaped Politics Policy.
Keywords: Supervision, Regulation, Regional Head